3x+4(2x-3)=6

Simple and best practice solution for 3x+4(2x-3)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+4(2x-3)=6 equation:


Simplifying
3x + 4(2x + -3) = 6

Reorder the terms:
3x + 4(-3 + 2x) = 6
3x + (-3 * 4 + 2x * 4) = 6
3x + (-12 + 8x) = 6

Reorder the terms:
-12 + 3x + 8x = 6

Combine like terms: 3x + 8x = 11x
-12 + 11x = 6

Solving
-12 + 11x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 11x = 6 + 12

Combine like terms: -12 + 12 = 0
0 + 11x = 6 + 12
11x = 6 + 12

Combine like terms: 6 + 12 = 18
11x = 18

Divide each side by '11'.
x = 1.636363636

Simplifying
x = 1.636363636

See similar equations:

| 2(f-9)=-24 | | 4=x^4 | | 3+2y-24=14 | | 7+3x=7x-29 | | 45=x-36 | | 6c-1=23 | | 216=5x | | -3(2t+3)=-3 | | -133=-7(6n+7) | | -2x+3(3x-6)=-2-9x | | 10(s-4)=-85 | | 2m-8=10+18 | | 3x+1y=392 | | 14x-9=11y | | 900000000000000000000000000000000+423523542546224624246426264462264264642426264426565374676585798966975685362431432134245436356457764575976980=x | | k-3(5)=12(5) | | 7-3x=x+3x | | X^2+11X+19=X-6 | | 7r+2=(5r-4) | | 8(3-5m)= | | 2(3x+3)+6(x-4)= | | 8x+17=-5(3-8x) | | 8.1-1.5x=-6.9 | | 3x^3+x^2-2=0 | | 2*5+x= | | -4(5y-6)-y=-3(y-4) | | 42y+4=16 | | 42y+4=17 | | 6.2m+3-1.9=-5.72 | | 8y=y+6+3 | | -(-(-k))-(-2)(-2+k)=-k-(4k+3) | | -2(6y-5)-y=-4(y-3) |

Equations solver categories